Hollow Pt Nanostructure‐decorated MWNT Electrode for Amperometric Hydrogen Detection. (24th November 2015) - Rashid, Muhammad; Bui, Trung Tuyen; Hoang, Anh Tuan; Seong, Gi Hun; Lim, Dong Woo; Kim, Yong Shin
Abstract :